Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar dan Aktivitas Visual Siswa pada Konsep Sistem Indra - Suriani Siregar (Universitas Islam Negeri Ar-Raniry, 2015)
This research aims to know the differences between learning outcomes and visual activity of students that learned through talking stick model of learning and the students that learned through conventional methods on the concept of the human sensory system. This study was conducted in SMA Negeri 1 Putri Betung in Academic year 2014/2015. This is an experimental research a with pretest posttest control group. The sample was chosen by using random cluster sampling technique. The sample of this research was students from class XI IPA1 as control class and class XI IPA2 as exsperimental class. The data for learning outcomes were obtained by using multiple choice test, while the data of students’ visual activity were gathered by using observation sheet. The data were analyzed by using t-test (independent t-test). The results showed that: (1) there are significant differences in learning outcomes between students that learned through talking stick model and students that learned through conventional methods in the concept of sensory system. The average of experimental class was 80.89 and control class was 71.71. the t-test obtained was =tcount = 2.475 > ttabel = 2.01, (2) there are differences in visual activity of students that learned by talking stick model of learning with students that learned through conventional methods on the concept of the human sensory system can be seen from average grade of experimental class was 74.63 while control class was 66.43. The t-test obtained was tcount = = 2,258 > ttable = 2,01.